To bend or not to bend – are heteroatom interactions within conjugated molecules effective in dictating conformation and planarity?. Issue 4 (4th May 2016) - Conboy, Gary; Spencer, Howard J.; Angioni, Enrico; Kanibolotsky, Alexander L.; Findlay, Neil J.; Coles, Simon J.; Wilson, Claire; Pitak, Mateusz B.; Risko, Chad; Coropceanu, Veaceslav; Brédas, Jean-Luc; Skabara, Peter J.
Abstract : The role of heteratoms in defining the conformation in conjugated structures is discussed. Abstract : We consider the roles of heteroatoms (mainly nitrogen, the halogens and the chalcogens) in dictating the conformation of linear conjugated molecules and polymers through non-covalent intramolecular interactions. Whilst hydrogen bonding is a competitive and sometimes more influential interaction, we provide unambiguous evidence that heteroatoms are able to determine the conformation of such materials with reasonable predictability.